Synthesis and characterization of superporous hydrogels by using gas blowing method - Najahusna, Adnan (2021)
Superporous hydrogels (SPHs) is a three-dimensional network of a hydrophilic polymer that absorbs a large amount of water in a very short period due to the presence of interconnected microscopic pores. The invention of superporous hydrogels is made up for modification of superabsorbent polymers (SAPs) due to the slow swelling properties. The present SAP contains less porous structure, thus produced slow swelling properties of the SAPs. The swelling rate of most SAPs is typically low and takes a longer time to reach equilibrium due to the slow water absorption capability. This disadvantage further limits the possible application of the hydrogel to be utilized in various fields, including as drug delivery material and as soil conditioner in agriculture. Therefore, there is a significant interest in developing synthesis methods and the selection of material in preparation of the SPH that can produce fast swelling absorption properties. In this study, SPHs were prepared from monomer of acrylamide (AM) and co-monomer acrylic acid (AA) by using gas blowing method with ammonium persulphate (APS) as an initiator and N’N’-methylenebisacrylamide (MBA) as cross linker. The effects of sodium bicarbonate (NaHCO3) concentration (0 wt% - 5 wt%) as foaming agent, acetic acid (0 wt% - 5 wt%) as foaming aid and Span 80 (0 wt% - 7.5 wt%) as foam stabilizer were studied by determined the water absorbency, morphology (SEM), compression strength, functional group (FTIR), thermal stability (TGA) and swelling kinetics of SPHs. Based on the optimum results, it shows that effect of foaming agent (NaHCO3) optimum at 4 wt% (178g/g) while effect of foaming aid optimum at 0 wt% as the addition of acetic acid has no significant difference with 0 wt%. then, the effect of foaming stabilizer (Span 80) optimize at 4.5 wt% where it gives the highest water absorbency at 206 g/g. The factor that contributed to the high water absorbency is mainly due to the formation of various sizes of pores in the structures of SPHs which allow the penetration of water which characterized by SEM. Based on the morphology results, the final 4.5 wt% Span 80 SPHs produce higher water absorbency due to present of many pore with uniform size in the SPHs structures. Then, the swelling rate also supports the foaming stabilizers effect as the 4.5 wt% Span 80 gives the higher water absorbency at shorter time. Lastly, the swelling kinetics results show that the SPHs obeyed the second order with diffusivity value, n is less than 0.5 as indicates that it follows the Fick’s Law. As a conclusion, SPHs prepared by gas blowing technique gave better performance of pore formation on superporous hydrogels.